The Horns of Moses - Jefferson, Lee M. (2023)
Whenever visitors arrive at the Church of St. Peter-in-Chains in Rome, they are struck with the grandeur of Michelangelo’s sculpture of Moses but ultimately are vexed by his appearance. Why does Moses have horns on his head? In our contemporary context, horned figures often represent devils and demons. Most docents or tour guides would […]
Keywords: Antisemitism; CHRISTIAN art & symbolism; Michelangelo Buonarroti, 1475-1564; MOSES (Biblical leader); MOSES (Biblical leader) in the New Testament; MOSES in art